Conclusion to special issue: "To the district… and beyond!". Issue 4 (December 2016) - Brack, Nathalie; Costa, Olivier; Kerrouche, Eric
Abstract This article summarizes the contributions of this special issue on MPs' local work in Belgium, France and Germany. In so doing, it highlights four elements to be taken into account when studying constituency representation: the MPs' incentives related to personal vote and the electoral system but also other motivations; the content of the MPs' activities on the ground; the impact of the district's characteristics; and, finally, the influence of the MPs' career path and institutional position. It proposes further avenues for future research.